COMMUNITY BASED ECOTOURISM IN THE SUNDARBANS OF BANGLADESH (RAJAGIRI JOURNAL OF SOCIAL DEVELOPMENT, 2012)
This paper discusses community based ecotourism in one of the environmentally important spots in the world - the Sundarbans of Bangladesh. The discussion is based on available literature and the results of an empirical study conducted by the authors in a local community of the Sundarbans. Some of the local people in the Sundarbans have taken up activities of ecotourism as secondary occupation during the tourist season in order to increase their meagre income. The main ecotourism activities undertaken by the local community are selling products of local handicrafts, cultural shows, amusement programmes and tour guidance. On the whole, the respondents of the study felt that ecotourism has had some impact on the socio-cultural and economic life of their community. However, they had mixed views on the nature of the impact (positive or negative) on the different aspects of their socio-cultural and economic life. While the impact on the economic aspect was perceived to be generally positive, the opposite was the position regarding the impact on culture and traditions. In view of the tremendous scope for ecotourism, both the government and the non-government agencies involved in the general tourism sector should work together in order to develop community based ecotourism in the Sundarbans.